Jóvenes, acciones y movimientos : aproximaciones desde el sur de México - Gómez-Abarca, Carlos de Jesús (CLACSO, 2021)
This book, as its author declares in the introduction, proposes a sociopolitical approach to Chiapas from a generational perspective, and part of its power lies in this: providing a generational perspective to understand the political processes located in the Chiapas temporal and spatial aspect; a point of view that is not centered on, by or for the youth, but rather builds an approach of and from the youth. In the chapters that follow, the reader will find approaches to ways of life and youth productions, modes of participation and modalities of approach to generational processes that will contribute to transforming the unequal realities in which we live, recognizing the diversities and differences that characterize youth. contemporary and instituting the common as other ways of being together.